Wild flood to graded border irrigation for water and energy conservation in the Klamath Basin - Smesrud, Jason, author; Madison, Mark, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
A large percentage of pasture in the Upper Klamath Basin is irrigated by "wild flood" surface irrigation methods. Efforts underway to improve irrigation efficiency in the basin using federal funds have included conversions to sprinkler irrigation systems and to higher efficiency graded border surface irrigation systems. With dramatic increases in power rates for agricultural users on the horizon, surface irrigation enhancements have significant promise to increase water use efficiency without substantially increasing production costs. While these projects generally do not solve the basin's water supply problems, they do provide a significant enhancement to surface water quality by reducing sediment and nutrient containing surface return flows. In areas where groundwater levels are declining due to irrigation pumping, these projects can also reduce stresses on groundwater supplies. A project implemented near Sprague River is used as a case study to describe how the simple conversion from ditched to piped laterals, creation of new border ridges, and improvements to irrigation scheduling can dramatically increase irrigation application efficiency while at the same time reducing pumping costs and groundwater withdrawals without any increase to daily labor requirements.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.